ASPEK SANITASI DAN HYGIENE DI WARUNG MAKAN IKAN LAUT KAWASAN PANTAI LEBIH KABUPATEN GIANYAR - Kesuma, I Wayan Agus Wijaya Adi; Wrasiati, Luh Putu; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): DesemberDO - 10.24843/JRMA.2018.v06.i04.p10, 2018)
The aim of this study was to determine the level of knowledge of sanitation and hygiene aspects to food handlers and food stall owners in marine food stalls in Pantai Lebih area, Gianyar Regency. The method used is a non-probability type of saturated sampling. Questionnaires were distributed to the food handler and the measurement method used a dichotomy scale that had 2 answers, namely "Yes" and "No".  Determination of the sample population was the entire restaurant located in the Pantai Lebih area and which was surveyed as food handlers.  The type of research in Pantai Lebih food stall was descriptive which explained the state of sanitation and hygiene. The results of the study showed that in the marine fish food stalls in Pantai Lebih of Gianyar Regency Sanitation facilities for marine fish food stalls in Pantai Lebih, Gianyar Regency 93,75% had fulfilled the requirements. In storing food ingredients, storing finished food, transporting food 100% food stalls already met hygiene requirements. The food service Food 97,5% of food stalls had met hygiene requirements. Food processing 75% of food stall shad met hygiene requirements. Procurement of new food ingredients 56,25% had met hygiene requirements. Key words : sanitation, hygiene, seafood stall, Lebih.